Is malnutrition associated with postoperative complications in patients with primary bone sarcomas?. Issue 3 (16th December 2018) - Park, Andrew; Lans, Jonathan; Raskin, Kevin; Hornicek, Francis; Schwab, Joseph; Lozano Calderon, Santiago
Abstract : Background: Modifiable risk factors that can be optimized to minimize postoperative complications in patients with bone sarcomas are yet to be identified. Methods: We retrospectively identified 275 patients aged 18 and older who underwent surgery for primary bone sarcomas who also had albumin values recorded within 4 weeks before surgery. Postoperative complications were defined as infection, hematoma, need for additional surgery, or wound complications. Results: In the multivariate analysis, age ( P  = 0.049) and neoadjuvant radiotherapy ( P  = 0.008) were independently associated with postoperative complications. We then performed a subanalysis of patients without a pelvic tumor who also did not receive radiotherapy ( n  = 178). In this population, albumin less than 2.8 g/dL was found to be independently associated with postoperative complications (odds ratio [OR], 4.69. 95% confidence intervals [CI], 1.03‐21.97; P  = 0.046). Conclusions: This study demonstrates that hypoalbuminemia (albumin < 2.8 g/dL) is associated with postoperative complications in patients with nonpelvic bone sarcomas who do not receive radiation. Future studies are necessary to further elucidate the role of nutrition, and they may show that nutritional status is a modifiable risk factor that can be optimized to improve the outcome of surgery for primary bone sarcomas.